Peroxynitrite-Dependent Zinc Release and Inactivation of Guanosine 5′-Triphosphate Cyclohydrolase 1 Instigate Its Ubiquitination in Diabetes - Zhao, Yu (American Diabetes Association, 2013)
Aberrant degradation of guanosine 5′-triphosphate cyclohydrolase 1 (GTPCH1) with consequent deficiency of tetrahydrobiopterin is considered the primary cause for endothelial dysfunction in diabetes. How GTPCH1 becomes susceptible to the degradation remains unknown. We hypothesized that oxidation and release of the zinc ion by peroxynitrite (ONOO(−)), a potent oxidant generated by nitric oxide and superoxide anions, instigates GTPCH1 ubiquitination and degradation. Zinc contents, GTPCH1 ubiquitination, and GTPCH1 activity were assayed in purified GTPCH1, endothelial cells, and hearts from diabetic mice. Exogenous ONOO(−) dose-dependently released zinc, inhibited its activity, and increased the ubiquitin binding affinity of GTPCH1 in vitro and in endothelial cells. Consistently, high glucose (30 mmol/L) inhibited GTPCH1 activity with increased ubiquitination, which was inhibited by antioxidants. Furthermore, mutation of the zinc-binding cysteine (141) (C141R or C141A) significantly reduced GTPCH1 activity and reduced its half-life but increased GTPCH1 ubiquitination, indicating an essential role of the zinc ion in maintaining the catalytic activity and stability of GTPCH1. Finally, GTPCH1 ubiquitination and degradation markedly increased in parallel with decreased GTPCH1 activity in the aortas and hearts of diabetic mice, both of which were attenuated by the inhibitors of ONOO(−) in mice in vivo. Taken together, we conclude that ONOO(−) releases zinc and inhibits GTPCH1, resulting in its ubiquitination and degradation of the enzyme.